THE APPLICATION OF CONTRASTIVE ANALYSIS THE CASE OF LEARNING LATIN LANGUAGE - Lumban Raja, Viator; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2021)
This paper tries to answer the question whether or not the Contrastive Analysis Theory can be applied in the methodology of teaching all languages universally. Some linguists and methodologists of teaching such as Lado, Fries, Lee, Corder, Stockwell and Martin, claimed that this theory is applicable in teaching second or foreign language. This paper will argue that it is not, and it will be supported with an example of the case I learning Latin language.